Effect of humic acid on the adsorption of selenium by lepidocrocite - Shengmao Zhao; Jian Zhu; Elias Niyuhire; Ruyi Zheng; Wenjian Mao (Archives of Environmental Protection)
Selenium (Se) mobility and bioavailability in natural environments are influenced by its adsorption at the aqueous interface of lepidocrocite (Lep), which is significantly affected by humic acid (HA), a common natural organic matter (NOM). This study investigated the mechanisms by which HA influences Se adsorption on Lep, aiming to understand how HA affects Se speciation, distribution, and mobility in natural environments. Batch experiments were conducted using synthetic Lep and HA under varying pH values (4-8) and HA concentrations (10-100 mg C/L). Interactions among HA, Lep, and Se were characterized using Fourier-transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Zeta potential and hydrodynamic diameter measurements were also performed to evaluate colloidal stability. HA significantly reduced Se adsorption on Lep by competing for adsorption sites, forming coordination bonds with Se, and altering Lep’s surface charge and hydrophobicity. At higher HA concentrations, dissolved and colloidal Se increased, while particulate Se decreased. Lower pH enhanced Se adsorption due to protonation, whereas higher pH promoted Se mobility. FTIR and SEM analyses confirmed HA’s role in modifying Lep’s surface properties and influencing Se adsorption behavior. HA plays a critical role in modulating Se adsorption on Lep through competitive adsorption, coordination interactions, and surface modification. These mechanisms influence Se speciation, distribution, and mobility, with implications for managing Se bioavailability in agricultural and environmental systems. This study provides insights into the geochemical cycling of Se and offers guidance for optimizing Se-rich agricultural practices.